Promoting new crop cultivars in low-income countries requires a transdisciplinary approach - Kholová, Jana; Urban, Milan; Bavorová, Miroslava; Ceccarelli, Salvatore; Lutomia, Cosmas; Desczka, Sabine; Grando, Stefania; Lensink, Robert; Nchanji, Eileen Bogweh; Pavlík, Jan; Pelaez, Diana; Rubyogo, Jean-Claude; et al. (Nature Portfolio, 2024)
The development of high-yielding, resilient cultivars is the primary goal of many crop breeding programmes, but the uptake of these new cultivars is persistently low in low-income countries. We discuss constraints related to the adoption of crop cultivars and stress the importance of participatory approaches in building trust and promoting the adoption of new technologies.